Governing through Penal Policy: Criminal Law and State Control Mechanisms - Henny Saida Flora; Pramidazzura Alifa Rifqi (PT. Anagata Sembagi Education, 2026)
Contemporary criminal law increasingly functions not only as an instrument for addressing crime but also as a mechanism of state control. The phenomenon of governing through penal policy reflects a shift in the role of criminal law from ultimum remedium toward a regulatory tool used to manage social behavior and political stability. This article examines the normative ambiguity surrounding the legitimacy of penal policy as a means of governance and its implications for the rule of law and human rights protection. Employing a normative juridical approach with critical and prescriptive analysis, the study reveals that the expansion of criminalization often lacks clear normative parameters, leading to overcriminalization, erosion of civil liberties, and legal uncertainty. Such developments risk undermining the legitimacy of criminal law and transforming it into an instrument of power rather than justice. The article argues for the necessity of normative limits on penal policy through the reaffirmation of the ultimum remedium principle, proportionality, and constitutional review mechanisms to safeguard democratic legal order and human rights.